THE IMPLEMENTATION OF ROBOTIC PROCESS AUTOMATION (RPA) AND ANALYTIC HIERARCHY PROCESS (AHP) FOR PROJECT PRIORITIZATION IN BANK SASA - Haikel, Syem
Robotic Process Automation (RPA) is a technology that configures a “robot” to emulate and integrate the actions of a human interacting within digital systems to execute a business process. It was an innovation in Bank SASA for digital transformation. The primary purposes are efficiency and mitigating risks to the bank because most banking transactions are repetitive tasks and have high transaction volumes. It takes much time consumed and could increase the probability of human error. Bank SASA’s managements wish that RPA can replace their employees to do those tasks and let them do more strategic and analytical jobs. To implement RPA technology, Bank SASA established a department at the beginning of 2020, namely the RPA Office, to focus on implementing RPA.